2017
DOI: 10.1039/c7dt03136j
|View full text |Cite
|
Sign up to set email alerts
|

The growing importance of crystalline molecular flasks and the crystalline sponge method

Abstract: This article showcases recent advancements made using crystalline molecular flasks and the widening list of prospective applications for the crystalline sponge method. This expansion has coincided with an increasing number of materials termed crystalline sponges, and a report of a predictive means of identifying candidates from crystallographic databases. The crystalline sponge method's primary application has been determination of absolute configuration, and this has evolved from the analysis of carefully cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…These design features are, generally, coupled with a high degree of crystallinity that allows for X-ray diffraction methods to be employed as a technique for the structural elucidation of guests. [33][34][35][36] The concept of using MOFs as crystalline scaffolds for the characterisation of guests is established. There are several examples where single crystal X-ray diffraction (SCXRD) has been employed to structurally identify the initial stages of gas adsorption, 37 MOF-adsorbate binding sites 38 and molecules absorbed from solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These design features are, generally, coupled with a high degree of crystallinity that allows for X-ray diffraction methods to be employed as a technique for the structural elucidation of guests. [33][34][35][36] The concept of using MOFs as crystalline scaffolds for the characterisation of guests is established. There are several examples where single crystal X-ray diffraction (SCXRD) has been employed to structurally identify the initial stages of gas adsorption, 37 MOF-adsorbate binding sites 38 and molecules absorbed from solution.…”
Section: Introductionmentioning
confidence: 99%
“…There are several examples where single crystal X-ray diffraction (SCXRD) has been employed to structurally identify the initial stages of gas adsorption, 37 MOF-adsorbate binding sites 38 and molecules absorbed from solution. 34,36,39,40 However, there is signicant scope for the development of MOFs as isolation matrices for metal-based moieties that are unstable in solution (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] However,i ns everal cases,t he determination of the guest species remains av ery demanding task [4] owing to the weak host-guest intermolecular interactions,mainly H-bonds, halogen-bonds,o rp-p interactions very often characterized by as ignificant positional disorder, [30] large thermal motion, and low occupancy. [4] Even though several works focusing on CSM have been presented so far, [18,19,[31][32][33] the analysis of the guest entering dynamics has not been explicitly investigated, [21,34,35] nor the formation of nanoconfined aggregates of the trapped molecules. [36,37] Recent works have shown that cutting-edge use of SCXRD allows the elucidation of inclusion processes occurring inside MOF cavities based on structural insight.…”
Section: Introductionmentioning
confidence: 99%
“…(The references cited here are a somewhat eclectic selection intended to illustrate the range of chemistry involved, rather than to be comprehensive, which is far from the case.) This has resulted not only in real advances towards practical objectives in gas storage [1,5,16,17] but also in unanticipated developments such as that of the "crystalline sponge" method [18,19] of determining the molecular structures of molecules otherwise difficult to crystallise. While metal ions clearly have a fundamental role in determining the structure of these materials, of equal importance is that they endow the solids with functionality specific to the given metal ion.…”
Section: Introductionmentioning
confidence: 99%